Bridging soil health gaps for resilient food systems in the Global South - Visscher, Anna Maria (2024)
Bridging soil health gaps is critical to enhance food security and climate resilience of smallholder farming systems in the Global South. However, there is a lack of agreement on what constitutes soil health and how to assess efficiently soil health (gaps) across diverse agroecological contexts and farming systems. We aimed (i) to synthesize key literature on soil health and approaches for its assessment ; (ii) present an operational framework involving relevant actors operating at different scales, and (iii) suggest research priorities for advancing soil health assessment and bridging soil health gaps to effectively support agronomic innovations that benefit smallholder producers in the Global South. We define soil health as the capacity of the soil to perform its multiple ecological functions within ecosystem and land use boundaries. We highlight that despite sharing the common overall goal of bridging soil health gaps, different actors have different needs and operate at different scales. We discuss available soil health indicators, focusing on their practical use, interpretation, and suitability and accessibility for different users and stakeholders and contexts. We propose a flexible framework that can be adapted to different contexts, guiding end- users in aligning their efforts to operationalize soil health. Finally, we address critical bottlenecks that require further research to enhance the advancement and practical application of the proposed framework, these include: 1) Approaches to benchmark and interpretate soil health indicators. 2) Linking soil health indicators to productivity and environmental outcomes, along with understanding the associated trade-offs; 3) Pathways to accelerate impact in soil health decision-making necessitates the development of robust, practical, and affordable indicators that fit the needs of actors with different resources available for soil health assessment.